The Concept and Principles of Universal Design - Badirovna, Isakova Muqaddas (International Journal on Orange Technologies, 2023)
This article will tell about the basic concept of universal design, methods of applying universal design in foreign experiments and situations that can be applied in a comfortable environment of people with disabilities in our country.